2022
DOI: 10.1021/acsami.2c13904
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pd–CoxOy Hybrid Nanostructure-Encapsulated Hollow Silica Nanospheres through Reverse Microemulsion Systems and Their Application as Efficient Hydrodechlorination Catalysts

Abstract: Pd–Co x O y heteroaggregate-encapsulated hollow porous silica nanoreactors (Pd–Co x O y @HPSNs) were synthesized by a reverse microemulsion system. The key design of the developed reverse microemulsion system is to use poly(ethyleneimine) in the water droplets as the void templates for silica deposition and for anchoring the catalytic functionality inside the hollow silica nanospheres. The synthesized Pd–Co x O y @HPSNs contain ∼3 nm Pd–Co x O y hybrid nanostructures in ∼10 nm central cavities of silica nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The adoption of COFs with specific functional groups and uniform pore size is critical for the anchor of metal NPs and their following hydrogenation application. Although either NaBH 4 , [43] or H 2 [44] or HCOOH [45] has been reported to work as hydrogen donor, the expensive, dangerous and corrosive features limit their practical applications. [46][47][48] In our case, ammonium formate (AF) is employed as an alternative one due to its low cost, safety and availability.…”
Section: Hydrogenation Reactions Over Aupd@cof Catalystsmentioning
confidence: 99%
“…The adoption of COFs with specific functional groups and uniform pore size is critical for the anchor of metal NPs and their following hydrogenation application. Although either NaBH 4 , [43] or H 2 [44] or HCOOH [45] has been reported to work as hydrogen donor, the expensive, dangerous and corrosive features limit their practical applications. [46][47][48] In our case, ammonium formate (AF) is employed as an alternative one due to its low cost, safety and availability.…”
Section: Hydrogenation Reactions Over Aupd@cof Catalystsmentioning
confidence: 99%
“…33,38 Compared with 0.5Pd/TiO 2 , the peak position over 0.5Pd/SiO 2 −TiO 2 (C) was shifted to lower binding energy by ∼0.5 eV, which suggests a stronger interaction existed between Pd and SiO 2 − TiO 2 (C). 9,39 The XPS speaks for 0.5Pd/SiO 2 −TiO 2 (C) can be divided into three separate peaks at 335.5, 336.6, and 341.8 eV, which are ascribed to Pd 0 and Pd 2+ , respectively. 7 The Pd 0 / (Pd 0 + Pd 2+ ) ratio over 0.5Pd/SiO 2 −TiO 2 (C) was about 6.2%.…”
Section: Xps Analysismentioning
confidence: 99%
“…Consequently, this synthesis yields ultrasmall bimetallic alloy nanoparticles with exceeding merits: exceptional size and compositional homogeneity, continuous tunability, and fully exposed metal surfaces. Previous studies have reported the synthesis of encapsulated metal nanoparticles in microemulsion systems, but most focused on monometallic metal nanoparticles, typically showing broad size distributions and often exhibiting multicore–shell configurations. Our experimental design, with thermodynamic control over both wet chemical and thermal alloying processes, enables the synthesis of ultrasmall bimetallic alloy nanoparticles with high precision, laying the foundation for fully controlling their catalytic properties. We demonstrate the outstanding catalytic performance of 1.2 nm-PtCo alloy nanoparticles in the chemoselective hydrogenation of 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF), an ideal platform for the synthesis of sustainable liquid fuels and chemicals from cellulose-derived HMF .…”
Section: Introductionmentioning
confidence: 98%